Challenges in particle physics and 3-3-1 models - Long, Hoang Ngoc (Communications in Physics, 2015)
At present, particle physics faces problems related with disparity in diphoton decay of Higgs boson, discrepancybetween theory and experiment of about 3.6 in anomalous magnetic moment of the muon and neutrino physics.Moreover, the existence of Dark Matter and the Matter-Antimatter Asymmetry are challenges for any physical model.In this review I present some solutions in the framework of the 3-3-1 models. The simple (by Higgs sector) models contain the hybrid inflationary scenario and the first-order phase transitions, from which leptogenesis needed for BAUis followed.By these considerations, some bounds on model parameters are derived.